SERIAL FOETAL GROWTH SCAN'S ACCURACY IN ESTIMATING FOETAL BIRTH WEIGHT IN MULTIPLE PREGNANCIES - Memon, Fouzia; Memon, Samreen; Lawley, Ruth (Journal of Postgraduate Medical Institute, 2018)
Objectives: To evaluate the role of ultrasonography (USG) in estimating foetal birth weight in twin pregnancies; and to classify the relationship of actual birth weight and estimated birth weight on ultrasonography. Methodology: It was an observational study on women with twin pregnancies who delivered from January 2009 till August 2018. Out of 27,219 women delivered at North Cumbria University Hospital, United Kingdom, a total of 870 sets of twin pregnancies were identified. We used customised growth chart software made by Perinatal Institute, United Kingdom for the plotting of foetal growth by USG. The estimated foetal birth weight (EFBW) measured on serial growth scans of twin pregnancies closest to the birth date was plotted on the customised growth charts. The EFBW at the time of delivery was predicted by following that centile and the difference between this EFBW and the actual weight was then assessed. Results: Of the 870 women with twin-pregnancy, majority were aged between 30-39 years (n=478, 55%). Primiparous women accounted for 470 (54%) and majority conceived naturally (n=690, 70%). Dichorionic diamniotic twins accounted for 565 (65%). In accordance with our acceptable standard of 250 grams, the majority of twins 64% of twin 1 and 78% of twin 2, the estimated birth weights by USG were within that standard. In 71% (618/870) of cases, the USG estimated birth weights in twin 1 were larger than the actual birth weight and similar picture was seen in 68% (592/870) of second twin. Conclusion: Ultrasound was found to be an accurate tool of determining estimated fetal birth weight. The majority of the USG estimated birth weights were within the agreed standard of 250g difference with the actual birth weight.